"Keeping My Accent?" Indonesian students' attitude and self-identity when speaking English in Malaysia: "Menjaga Aksen Saya?" Sikap dan Identitas Diri Mahasiswa Indonesia Saat Berbicara Bahasa Inggris di Malaysia - Aini Nabila Ikhwanudin; Nunung Suryati; Prof. Drs. Bambang Yudi Cahyono, M.Pd., M.A., Ph.D; Niamika El Khoiri (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study examines Indonesian students’ perceptions of their Indonesian-accented English (IAE) and how this accent reflects their linguistic identity while studying in Malaysia. Although English is widely used as a second language in Malaysia, Indonesian students often navigate a multilingual environment where accents serve as visible markers of identity and a potential source of judgment. The study aims to explore (1) students' attitudes towards their Indonesian accent when speaking English and (2) the extent to which they associate the accents with their cultural identity. A descriptive qualitative design was employed, using a Likert-scale questionnaire distributed to 36 Indonesian students at University Sains Malaysia and supported by semi-structured online interviews with four participants. Questionnaire data were analyzed using descriptive statistics, and interview responses were analyzed using thematic analysis. Results show that most students view their Indonesian accent positively and do not consider it a marker of poor English. Many reject the idea that IAE diminishes their credibility and instead consider it an authentic part of their cultural background. A smaller group, however, expressed discomfort or a desire to adopt more internationally dominant accents. Overall, the results highlight a growing acceptance of linguistic diversity aligned with English as a Lingua Franca principles. The study suggested that accent awareness, identity-affirming pedagogies, and inclusive language policies are essential in international education settings. These insights contribute to ongoing discussions about accent perception, linguistic identity, and native-speaker ideology in Southeast Asian Contexts.